Analysis of the Determinants of Knowledge, Accessibility, and Servive Quality on the Utilisation of Health Services with Socio-Economic Status as a Moderating Variable in BPJS Health Patients (Pusat Riset dan Inovasi Nasional, 2025)
Utilization of health services is influenced by various factors such as knowledge, accessibility, service quality, and socioeconomic conditions. Therefore, high Universal Health Coverage (UHC) coverage does not always correspond to increased utilization of health services. The phenomenon at QIM Batang Hospital shows a gap between almost universal UHC participation and service utilization that is still hampered by geographical factors, limited facilities, low public knowledge, and perceptions of service quality. The purpose of this study was to analyze the influence of knowledge, accessibility, and service quality on health service utilization by considering the role of socioeconomic factors as a moderator. This study was conducted at QIM Batang Hospital with a sample of 100 patients. Research data were obtained from questionnaires distributed to respondents and then analyzed using SEM-PLS analysis. The results showed that knowledge, accessibility, and service quality significantly influenced the utilization of health services by BPJS patients. Knowledge encourages patients' ability to make health decisions, accessibility determines ease of use of services, and service quality increases trust and continuity of utilization. The role of socioeconomic factors only moderates the relationship between accessibility and utilization, but does not affect the relationship between knowledge and service quality. These findings strengthen Andersen's theory regarding the role of predisposing factors, supporting factors, and socioeconomic characteristics. The implications of the research emphasize the importance of increasing health literacy, improving access, and strengthening the quality of services for the sustainable use of health facilities.